2014
DOI: 10.3390/agriculture4020096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spring Wheat (20 Varieties) Adaptation to Soil Drought during Seedlings Growth Stage

Abstract: Abstract:The effect of soil drought (10 days) on the growth of plants, the accumulation of water and leakage of electrolytes, gas exchange, the contents of chl a + b and carotenoids in leaves and photochemical activity of photosystem II was studied at the seedling stage by transient fluorescent analysis in 20 of the popular varieties of polish spring wheat. Drought caused a particularly strong reduction in vigor of growth of seedlings, net photosynthesis rate and triggered an increase in electrolyte leakage fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Additionally, the process by which a plant leaf achieves carbon gain via photosynthesis in relation to water loss through transpiration has been identified in this study as pWUE. The findings of the present investigation highlight that drought conditions led to a notable reduction in the pWUE of Shandawel 1, whereas Sakha 95 experienced a negligible decrease which aligns with studies that reported a downturn in pWUE for certain wheat strains under drought conditions [ 45 ]. This reduction in pWUE under drought circumstances might stem from the adverse impacts of stress on the rate of photosynthesis and transpiration.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the process by which a plant leaf achieves carbon gain via photosynthesis in relation to water loss through transpiration has been identified in this study as pWUE. The findings of the present investigation highlight that drought conditions led to a notable reduction in the pWUE of Shandawel 1, whereas Sakha 95 experienced a negligible decrease which aligns with studies that reported a downturn in pWUE for certain wheat strains under drought conditions [ 45 ]. This reduction in pWUE under drought circumstances might stem from the adverse impacts of stress on the rate of photosynthesis and transpiration.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, drought stress treatment in three different stages of growth significantly reduced average values of GYP, BWP, WUEb, WUEg and HI in all tested genotypes. BIESAGA-KOŚCIELNIAK et al (2014) also reported a statistically significant decrease of GYP in 18 and WUE in all 20 of the tested wheat varieties caused by drought stress, when compared to the properly watered controls.…”
Section: Drought Stress and Agronomic Traits Of Winter Wheat Cultivarsmentioning
confidence: 76%
“…Hassan et al 24 ; El-Hamamsy and Behairy, 25 and Alamri et al 26 illustrated that seedling vigor traits and tissue water content decreased with increasing of PEG and NaCl concentrations. Biesaga-Kościelniak et al, 27 reported that wheat seedlings under drought stress had considerably decreased growth vigour. Studies of correlation between several variables (Table 2) revealed a favourable and highly significant relationship between seedling length and vigour index.…”
Section: Resultsmentioning
confidence: 99%